EFEKTIVITAS EKSTRAK ETANOL DAUN SERUNAI (Chromolaena odorata L.) SEBAGAI ANALGETIKA - Rusdiati Helmidanora; Chairunnisa; Yullia Sukawaty (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Chromolaena odorata L. leaves contain the main compounds, namely flavonoids, saponins, triterpenes, steroids and tannins. Leaves Chromolaena odorata L. has antelmintic, antimalarial, analgesic, anti-inflammatory, antipyretic, antispasmodic, antimicrobial, anti-fungal and diuretic activities. The analgesic effect of the leaves of Chromolaena odorata L. comes from the flavonoids contained in it. The extraction method of Chromolaena odorata L.leaves was carried out by maceration using 70% alcohol, which aimed to determine the effectiveness of Chromolaena odorata L. leaf extract as an analgesic in male white rats. This research is experimental with the method of collecting leaf samples with purposive sampling. Using test animals, white mice were divided into 5 groups (positive control (potassium diclofenac), negative control (0.5% Na-CMC), dose (50 mg/kg body weight, 100 mg/kg body weight and 200 mg/kg body weight), induced by using 0.5% acetic acid, the analgesic power was calculated based on the number of stretching mice for 1 hour. the data obtained were analyzed using the Kruskal Wallis test. Ethanol extract of serunai leaves has potential effectiveness as an analgesic force for male white mice (p 0.043 > 0.05) with a percentage of analgesic strength at a dose of 50 mg/kg BB (28.5%), a dose of 100 mg/kg BB (58.8%), a dose of 200 mg/kg BB (67.3%).